ANALISIS KOMPETENSI KOMUNIKASI CUSTOMER SERVICE DALAM MENINGKATKAN KEPUASAN PELAYANAN NASABAH PT. BANK CENTRAL ASIA TBK. - FIRMAN PRASETYO (2021)
In improving a service to customers, a customer service must perform excellent service that can improve service to customers. Viewed from the point of view of a customer the service provided by a customer service must do the best service because if a customer service performs service to the maximum then a customer will get his own satisfaction with the services provided. The satisfaction of a customer can be determined from the quality of the services they have, so we must prioritize, because the services we provide are a benchmark for excellence in industry competition that also provides services. As part of the banking industry, PT Bank Central Asia Tbk. must continue to improve the quality of customer service, because customer satisfaction is influenced by services from customer service and employees.